Pan-caspase inhibition during normothermic machine perfusion of discarded livers mitigates ex situ innate immune responses - Raigani, Siavash; Santiago, John; Ohman, Anders; Heaney, Megan; Baptista, Sofia; Coe, Taylor M.; de Vries, Reinier J.; Rosales, Ivy; Shih, Angela; Markmann, James F.; Gruppuso, Philip; Uygun, Korkut; et al. (Frontiers in Immunology, 2022)
Access to liver transplantation is limited by a significant organ shortage. The recent introduction of machine perfusion technology allows surgeons to monitor and assess ex situ liver function prior to transplantation. However, many donated organs are of inadequate quality for transplant, though opportunities exist to rehabilitate organ function with adjunct therapeutics during normothermic machine perfusion. In this preclinical study, we targeted the apoptosis pathway as a potential method of improving hepatocellular function. Treatment of discarded human livers during normothermic perfusion with an irreversible pan-caspase inhibitor, emricasan, resulted in significant mitigation of innate immune and pro-inflammatory responses at both the transcriptional and protein level. This was evidenced by significantly decreased circulating levels of the pro-inflammatory cytokines, interleukin-6, interleukin-8, and interferon-gamma, compared to control livers. Compared to emricasan-treated livers, untreated livers demonstrated transcriptional changes notable for enrichment in pathways involved in innate immunity, leukocyte migration, and cytokine-mediated signaling. Targeting of unregulated apoptosis may represent a viable therapeutic intervention for immunomodulation during machine perfusion.